The MAPK Pathway Signals Telomerase Modulation in Response to Isothiocyanate-Induced DNA Damage of Human Liver Cancer Cells - Lamy, Evelyn; Herz, Corinna; Lutz-Bonengel, Sabine; Hertrampf, Anke; Márton, Melinda-Rita; Mersch-Sundermann, Volker (PLOS ONE, 2013)
4-methylthiobutyl isothiocyanate (MTBITC), an aliphatic, sulphuric compound from Brassica vegetables, possesses in vitro and in vivo antitumor activity. Recently we demonstrated the potent growth inhibitory potential of the DNA damaging agent MTBITC in human liver cancer cells. Here we now show that MTBITC down regulates telomerase which sensitizes cells to apoptosis induction. This is mediated by MAPK activation but independent from production of reactive oxygen species (ROS). Within one hour, MTBITC induced DNA damage in cancer cells correlating to a transient increase in hTERT mRNA expression which then turned into telomerase suppression, evident at mRNA as well as enzyme activity level. To clarify the role of MAPK for telomerase regulation, liver cancer cells were pre-treated with MAPK-specific inhibitors prior to MTBITC exposure. This clearly showed that transient elevation of hTERT mRNA expression was predominantly mediated by the MAPK family member JNK. In contrast, activated ERK1/2 and P38, but not JNK, signalled to telomerase abrogation and consequent apoptosis induction. DNA damage by MTBITC was also strongly abolished by MAPK inhibition. Oxidative stress, as analysed by DCF fluorescence assay, electron spin resonance spectroscopy and formation of 4-hydroxynonenal was found as not relevant for this process. Furthermore, N-acetylcysteine pre-treatment did not impact MTBITC-induced telomerase suppression or depolarization of the mitochondrial membrane potential as marker for apoptosis. Our data therefore imply that upon DNA damage by MTBITC, MAPK are essential for telomerase regulation and consequent growth impairment in liver tumor cells and this detail probably plays an important role in understanding the potential chemotherapeutic efficacy of ITC.